LINGVOCOGNITIVE AND LINGUOCULTURAL STUDY OF MEASUREMENT UNITS IN ENGLISH AND UZBEK LANGUAGES - Nazarov, Behzod (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
This study investigates the lingvocognitive and linguocultural aspects of measurement units in English and Uzbek languages, highlighting the interplay between language, culture, and cognition. By analyzing semantic structures, idiomatic expressions, and cultural contexts, the research reveals how measurement units reflect the worldview of English- and Uzbek-speaking communities. The findings contribute to a deeper understanding of cross-linguistic and cross-cultural communication.